Strategy to Improve the Quality of Educational Program of PGMI Study at UIN Sayyid Ali Rahmatullah Tulungagung through the Mbkm Program - Nita Agustina Nurlaila Eka Erfiana; Liatul Rohmah (CV. Creative Tugu Pena, 2026)
This study aims to analyze the strategy for improving the quality of education in the PGMI Study Program at UIN Sayyid Ali Rahmatullah Tulungagung through the implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) program. This study uses a qualitative approach with a case study method, where data were collected through in-depth interviews with stakeholders, participant observation, and document review. The results reveal that the quality improvement strategy is implemented through four main approaches. First, strengthening the capacity of lecturers and curriculum integrated with the student exchange scheme. Second, optimizing the recruitment process and academic mentoring for students participating in the MBKM program. Third, creating a flexible credit transfer and learning recognition system. Fourth, developing strategic partnerships with partner universities. The implementation of the MBKM student exchange program has been proven to have a significant impact on improving student competency in aspects of hard and soft skills, enriching academic insight, and strengthening professional networks. This program also encourages learning innovation and revitalizing the PGMI Study Program curriculum. The findings of this study recommend the importance of strengthening support systems, increasing access to information, and sustainable budgeting to maximize the impact of the MBKM program on improving the quality of Islamic higher education